REPRESENTASI NILAI NASIONALISME DALAM KARYA FILM PENDEK “NDUDAH KIDUNGE SIMBAH” - hermawan, antok; Hayau Lailin, Moch. Ichdah Asyarin (Program Studi Ilmu Komunikasi Universitas Islam Majapahit, 2024)
Local films can serve as an effective means of communicating messages, especially in terms of encouraging the spirit of nationalism in the younger generation. One of them is by using short films as a medium. This research takes the object of a short film entitled